Pengaruh Kualitas dan Harga terhadap Keputusan Pembelian - Siti Nurjanah; Umban Adi Jaya (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Purchase decisions are actions taken by consumers to make a purchase of a product. Therefore, consumer purchasing decision making is a process of selecting one of several alternative problem solving with real follow-up. The purpose of this study was to determine the effect of quality and price in the buying process and to collect supportive research on the influence of quality and price on purchasing decisions. The method that researchers use is SLR (Systematic Literature Review). The results of the research conducted in this review are getting a lot of literature that there is a significant influence on quality and price on purchasing decisions. The quality of a product or the quality of a product is the physical condition, function and nature of a product in question that meets the tastes and needs of consumers in accordance with the value for money that has been issued. Price can be an indicator of product quality. Consumers usually identify the price of an expensive product with good quality and if the price of the product is cheap, the consumer doubts the quality. If the price is too expensive, consumers will see the quality and price match.